2022
DOI: 10.3390/foods11162409
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Check-All-That-Apply (CATA) Ballot and Machine Learning for Generation Z Consumers for Innovative Traditional Food

Abstract: Generation Z (Gen Z) consumers account for an increasing proportion of the food market. The aim of this study took lamb shashliks as an example and developed novel products from the perspective of cooking methods in order to develop a traditional food suitable for Gen Z consumers. The sensory characterization of electric heating air (EH), microwave heating (MH), air frying (AF), and control (traditional burning charcoal (BC) of lamb shashliks) was performed using the CATA methodology with 120 Gen Z consumers a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…Compared to the control sample T, sample K ranked second in the attribute ratings of umami flavor, intensity odor, dark appearance, roasting-lamb odor, and juicy appearance. Based on the findings of Wang et al (2022) , consumers were attracted to lamb shashliks treated by the K method due to their buttery odor, making them unique and popular. Among the samples, sample L presented the highest fatty odor (8.4), the second greasy appearance (8.4), the second fatty flavor (8.3), and the second buttery odor (7.9).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Compared to the control sample T, sample K ranked second in the attribute ratings of umami flavor, intensity odor, dark appearance, roasting-lamb odor, and juicy appearance. Based on the findings of Wang et al (2022) , consumers were attracted to lamb shashliks treated by the K method due to their buttery odor, making them unique and popular. Among the samples, sample L presented the highest fatty odor (8.4), the second greasy appearance (8.4), the second fatty flavor (8.3), and the second buttery odor (7.9).…”
Section: Resultsmentioning
confidence: 99%
“…In a previous study, the buttery odor was identified as an important sensory attribute of lamb shashliks treated by the K method ( Wang et al, 2022 ). As a result of this attribute, consumers prefer lamb shashliks that have been treated with the K method.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Check-all-that-apply tests (CATA) were used to gain information about the characteristics of the chocolate aroma and flavor [17]. This easy technique avoids scaling problems often encountered by untrained people, as there is no demand to rate the intensity [18,19].…”
Section: Consumer Testmentioning
confidence: 99%